Draft genome sequence data of Streptomyces sp. FH025 - Goh, Lucky Poh Wah; Fauze Mahmud; Lee, Ping Chin (Elsevier, 2021)
The genome data of Streptomyces sp. FH025 comprised of 8,381,474 bp with a high GC content of 72.51%. The genome contains 7035 coding sequences spanning 1261 contigs. Streptomyces sp. FH025 contains 57 secondary metabolite gene clusters including polyketide synthase, nonribosomal polyketide synthase and other biosynthetic pathways such as amglyccycl, butyrolactone, terpenes, siderophores, lanthipeptide-class-iv, and ladderane. 16S rRNA analysis of Streptomyces sp. FH025 is similar to the Streptomyces genus. This whole genome project has been deposited at NCBI under the accession JAFLNG000000000.